CLINICAL COMPARATIVE STUDY IN THE MANAGEMENT OF KASHTARTAVA W.S.R. PRIMARY DYSMENORRHOEA WITH RUTUKARI VATI AND KUMARYASAVA - Patil, Shankramma; J.M, Pradeep; N.S, Manjunatha (International Journal of Ayurveda and Pharma Research, 2018)
Adolescence is the rapid growing period when mainly the physical changes are important. 95% girls attain menarche at the age group of 10 to 16 yrs, the peak being 13yrs. Among them, not less than 50% of female are said to experience some discomfort or pain in relation to menstruation. Kashtartava is a symptom mentioned in various Yoni vyapads, Vata being the main causative factor for this condition, which is commonly compared with dysmenorrhoea by cotemporary science. Conventional treatment of primary dysmenorrhoea consists of non-steroidal and anti-inflammatory drugs, hormonal therapy which causes unwanted side effects. Hence Rutukari Vati which is mentioned in Bheshaja Samhita for Kashtartava having the properties like, Vedanashamaka, Arthavajanana have been selected for the planned study.Design of Study: A Single blind comparative clinical study of two groups, trial and control, consisting of 15 subjects in each with pre-test and post-test design. Group A was given Rutukarivati and Group B was given Kumaryasava 25ml twice daily after food. Result: Rutukarivati contains most of the drugs with Tiktha and Katu rasa, Usnaveerya property and Vatakaphahara property; it is effective in controlling pain and regularizing the cycle. On comparison of overall effect of both groups has more significant result but percentage wise group A is more effective than group B. Mild increase in amount of bleeding was noted in patients in group A. It may be because of most of the ingredients in Rutukarivati are Artavajanana and Apanavatashaman.